Indoglish Phenomenon: The Adaptation of English into Indonesian Beauty Vlogger’s Content - RangRang Mirana; Otong Setiawan Djuharie Djuharie (Indo Publishing, 2026)
This study examines the phenomenon of “Indoglish” a term describing the adaptation of English into Indonesian language and culture (Saddhono & Hasanah, 2016) as it manifests in the spoken content of Indonesian beauty vloggers on YouTube. The research aims to identify the structural forms of code-mixing present in beauty vlogging discourse and to explain why English elements, rather than their Indonesian equivalents, are consistently favored across different content niches. A descriptive qualitative approach within a case study framework was adopted, drawing on 40 transcribed utterances (eight per channel) from tutorial, product-review, and “get ready with me” videos produced by five purposively selected Indonesian beauty vlogger channels representing distinct content niches ingredient-focused skincare, drugstore makeup, luxury beauty, K-beauty, and Gen Z casual content anonymized as Vlogger A through Vlogger E. The utterances were classified into the structural categories of insertion, alternation, and congruent lexicalization, following the typological approach applied in recent Indonesian code-mixing research (Putri & Putri, 2026; Putri et al., 2022), and interpreted through Hoffmann’s (1991) functional framework, encompassing topical, interjectional, emphatic, and group-identity motivations. The findings show insertion as the most dominant structural form, consistent with patterns reported among Indonesian beauty vloggers generally (Fauziah & Suryani, 2022) and TikTok Gen Z beauty influencers specifically (Putri & Putri, 2026), while congruent lexicalization recurs systematically through the Indonesian suffix -nya and prefix di-, echoing loanword adaptation processes documented for English entering Indonesian (Priyastuti, 2012). Beyond classification, the analysis shows that the choice of English over Indonesian is shaped jointly by lexical gaps in technical beauty vocabulary, the prestige and cosmopolitan positioning associated with the global beauty community, register variation across content niches, and the discourse economy demanded by fast-paced spoken narration. Functionally, English insertions serve topical, interjectional, emphatic, and group-identity purposes, echoing findings from studies of Indonesian university speech (Rakhmawati et al., 2016) and social media communication (Oktavia, 2019; Sudewi et al., 2023). Notably, prior research suggests that English insertion does not necessarily translate into stronger purchase intention among viewers, who instead value variety, humor, and honesty in content (Salikin, Wahyuningsih, & Poerwanta, 2023). The study concludes that Indoglish in Indonesian beauty vlogging content is a deliberate, niche-sensitive communicative resource that allows content creators to project expertise, relatability, and belonging within the online beauty community, even where its persuasive commercial power remains limited.